2002
DOI: 10.1002/pd.407
|View full text |Cite
|
Sign up to set email alerts
|

Decreased first trimester PAPP‐A is a predictor of adverse pregnancy outcome

Abstract: We conclude that decreased levels of first trimester maternal serum PAPP-A are predictive not only of chromosome anomalies but also of adverse pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
113
9
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 44 publications
25
113
9
7
Order By: Relevance
“…It is well accepted that low PAPP-A is associated with subsequent pregnancy loss (Ong et al, 2000;Yaron et al, 2002a;Kwik and Morris, 2003;Dugoff et al, 2004;Kabili et al, 2004;Liu et al, 2004). Our findings are compatible with these previous studies and demonstrated that a PAPP-A ≤0.3 MoM conveyed a significant risk of pregnancy loss almost five times greater than pregnancies with a PAPP-A >0.3 MoM.…”
Section: Low Papp-a and Adverse Outcomessupporting
confidence: 83%
See 2 more Smart Citations
“…It is well accepted that low PAPP-A is associated with subsequent pregnancy loss (Ong et al, 2000;Yaron et al, 2002a;Kwik and Morris, 2003;Dugoff et al, 2004;Kabili et al, 2004;Liu et al, 2004). Our findings are compatible with these previous studies and demonstrated that a PAPP-A ≤0.3 MoM conveyed a significant risk of pregnancy loss almost five times greater than pregnancies with a PAPP-A >0.3 MoM.…”
Section: Low Papp-a and Adverse Outcomessupporting
confidence: 83%
“…Increased risk of low birth weight, intrauterine growth retardation and premature birth in women with low PAPP-A has been noted by others (Dugoff et al, 2004;Kabili et al, 2004;Krantz et al, 2004). In contrast, other studies have found an association between low PAPP-A and increased risk of low birth weight or intrauterine growth retardation, but not with preterm birth (Ong et al, 2000;Yaron et al, 2002a;Kwik and Morris, 2003;Tul et al, 2003). Furthermore, Morssink et al (1998) concluded that PAPP-A is not associated with either fetal growth restriction or preterm delivery.…”
Section: Low Papp-a and Adverse Outcomesmentioning
confidence: 72%
See 1 more Smart Citation
“…Several recent studies have shown an association between low first-trimester maternal serum pregnancy associated plasma protein-A (PAPP-A) levels and the subsequent development of pregnancy complications, including pre-eclampsia Smith et al, 2002;Yaron et al, 2002;Tul et al, 2003;Dugoff et al, 2004;Krantz et al, 2004;Spencer et al, 2005aSpencer et al, , 2006aSpencer et al, ,b, 2007aCowans and Spencer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hospitalization for preterm contractions with suspected imminent preterm delivery poses a major burden on health services, and costs and accounts for more than one-third of obstetric admissions before delivery. 6,7 Although used in prenatal genetic screening programs since the 1980s 8 and also for risk assessment of preterm labor, 9 the predictive power of pregnancy-associated plasma protein A (PAPP-A) in the second trimester for preterm delivery is still considered speculative. 10 In assessing the predictive value of first-trimester PAPP-A for preterm delivery and fetal growth restriction in a selected study group of pregnancies achieved via assisted technologies, only weak associations have been found.…”
Section: Introductionmentioning
confidence: 99%